2023
DOI: 10.5455/javar.2023.j666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose and trehalose on tris-citric acid-egg yolk-fructose diluents for semen cryopreservation in goat

Abstract: Objectives: This study aimed to examine the impacts of the wide range of concentrations of glu¬cose and trehalose on the tris-citric acid-egg yolk-fructose (TCEF) extenders for cryopreservation of goat semen. Materials and Methods: The sperm sample was pooled, washed, and diluted in control (TCEF without glucose and trehalose), TCEF + glucose (75, 150, 450, and 900 mm), and TCEF + trehalose (75, 150, 450, and 900 mm). After equilibrations, the semen straws were frozen under LN2 in the LN2 tank. After LN2 stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
1
0
1
Order By: Relevance
“…The result also showed that utilizing disaccharides could maintain motility better than other saccharides this finding is also similar to previous research which stated lactose/disaccharide is the best saccharide type to preserve frozen semen (Lapwood and Martin, 1966), our result is in agreement with findings in boar that comparing monosaccharides and disaccharides on sperm quality of boar sperm cryopreserved with an egg yolk based extender (Gómez-Fernández et al, 2012) this occurs due to disaccharides more being able to cross the cell membrane than the trisaccharides also less easily converted into energy than monosaccharides thereby better able to maintain the membrane integrity of cells than other saccharides (Kamal et al, 2023). Disaccharides could prevent the formation of ice crystals by forming hydrogen bonds between molecules in the lipid bilayer of cryopreserved semen (Uchida et al, 2007).…”
Section: Semen Quality After Diluting Equilibrating and Thawingsupporting
confidence: 93%
“…The result also showed that utilizing disaccharides could maintain motility better than other saccharides this finding is also similar to previous research which stated lactose/disaccharide is the best saccharide type to preserve frozen semen (Lapwood and Martin, 1966), our result is in agreement with findings in boar that comparing monosaccharides and disaccharides on sperm quality of boar sperm cryopreserved with an egg yolk based extender (Gómez-Fernández et al, 2012) this occurs due to disaccharides more being able to cross the cell membrane than the trisaccharides also less easily converted into energy than monosaccharides thereby better able to maintain the membrane integrity of cells than other saccharides (Kamal et al, 2023). Disaccharides could prevent the formation of ice crystals by forming hydrogen bonds between molecules in the lipid bilayer of cryopreserved semen (Uchida et al, 2007).…”
Section: Semen Quality After Diluting Equilibrating and Thawingsupporting
confidence: 93%
“…Several extenders supplemented with various sugars have been used for the preservation of mammalian semen, including glucose (De los Reyes et al., 2002), lactose (Salamon & Maxwell, 2000), fructose (Ponglowhapan et al., 2004) and raffinose (Salamon & Maxwell, 2000). Furthermore, recently, sucrose and trehalose have been the most commonly used disaccharides for protecting semen mammals during the freezing process, such as pig (Pezo et al., 2020), ram (Jia et al., 2021) and goat (Kamal et al., 2023) (Table 3).…”
Section: Non‐permeable Cryoprotectant Agentsmentioning
confidence: 99%
“…No obstante, se han evaluado diversos azúcares como crioprotectores no penetrantes, entre los cuales se incluyen: glucosa, fructosa, lactosa y trehalosa (De mercado et al, 2010;Athurupana et al, 2015;Cantanhêde et al, 2018;Pezo et al, 2020;Kamal et al, 2023) donde, los que han dado mejores resultados en cerdos comerciales postdescongelación son la lactosa y la trehalosa, sin embargo, se desconocen los efectos de diferentes diluyentes sobre la calidad seminal del cerdo pelón mexicano . Por lo que, el objetivo fue evaluar diferentes azúcares en el diluyente de congelación para semen de cerdo pelón mexicano y su efecto sobre la calidad seminal a la descongelación.…”
Section: Introductionunclassified